A functional approach to analyze the genetic basis for differences in virulence of monkeypox virus clades - Patricia L. Earl; Jeffrey L. Americo; Sara Reynolds; Wei Xiao; Catherine Cotter; Bernard Moss (Emerging Microbes and Infections)
Mpox, the disease caused by monkeypox virus (MPXV) is increasing in Africa and in 2022 spread to more than 100 countries sickening more than 100,000 individuals. Four clades of MPXV have been recognized with differences in severity of disease and extent of human-to-human transmission. Determination of the genetic basis for these differences could help to develop improved therapeutics and vaccines. The Castaneous (CAST) mouse is highly susceptible to MPXV and virulence differences of MPXV clades are statistically significant mimicking their relative severities in humans. The present study was intended to evaluate the CAST mouse as a model for investigating genomic differences by replacing genes of Zaire-1979 005 (Z-79) clade Ia MPXV with homologous gene sequences of the less virulent and less transmissible USA-2003 clade IIa MPXV. The expectation was that some gene replacements would reduce the virulence of Z-79 chimera. Recombinant viruses expressing firefly luciferase were constructed in which partially overlapping Z-79 DNA segments of 5,000 to 13,000 bp containing ∼ 40 genes in total from the two ends of MPXV-79 were replaced with corresponding segments of USA-2003. Virulence was determined by live animal imaging in addition to weight loss and survival. Although there were statistical differences in survival and viral luminescence between the clade Ia and clade IIa MPXVs, no significant difference was found by replacing individual or multiple genes of clade Ia Z-79 with corresponding genes of clade IIa USA-2003. The absence of a significant reduction in virulence can have several explanations that would inform future experiments.